Geographical Factors and General Soedirman's Strategy in Second Dutch Military Aggression, 1948–1949 - Tari, Intan Sautrina (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
On December 19, 1948, Dutch military forces were able to capture major cities in Java and Sumatra but could not control rural areas or remote areas. It was their weakness, so General Soedirman used it to fight against the Dutch during the Second Military Aggression. This research aims to analyze the role of Indonesia's geographic conditions in General Soedirman's strategic achievement and its potential influence on Indonesia's defensive posture during the Second Dutch Military Aggression. The research method used in this article is qualitative, with a literature study approach of collecting information and conducting library research from books, historical documents, and journals. The results of the analysis show that the geographical characteristics of the Java region, which has a diverse landscape, provided ideal terrain for Soedirman's troops and became a driving force for Indonesia's success in facing the Dutch; this had the effect of exhausting the enemy and contributed to the military failure of the Dutch troops.